The role of project management office (PMO) manager: A qualitative case study in Indonesia - Mohammad Ichsan; Jimmy Sadeli; Gregorian Jerahmeel; Yesica Yesica (Cogent Business & Management, 2023)
In recent years, the need for PMOs in various organizations has increased due to the positive impact of PMOs on the projects being carried out. This phenomenon is also occurring in Indonesia, but it does not work the way PMO should. This study, therefore, attempts to provide the role of the PMO manager so that they can adequately carry out their task, as there is as yet no literature that specifically addresses the role of the PMO manager. This study uses descriptive qualitative research methodology by performing three main activities. First, determining the functions of PMO that were derived from 70 papers. Second, making the pre-FGD survey based on the findings from the literature review of the functions of PMO. Third, making focus group discussion (FGD) to discuss, validate the result of the pre-FGD survey, and determine the role of PMO manager. This study found 60 roles of PMO manager within the scope of the seven functions of PMO. Although the study was carried out as part of the PMO in Indonesia, the respondents were PMO Managers. practitioners, and academics from Indonesia, the findings contribute to the latest PMO literature developments and open up opportunities for future research on the PMO manager's competency framework.
Keywords: 650; Competency; PMO Competency; PMO Function; PMO Manager; PMO Roles